Pagans, Tartars, Moslems, and Jews in Chaucer's "Canterbury Tales": By Brenda Deen Schildgen (Gainesville: University Press of Florida, 2001. 183 pages.) (American Journal of Islam and Society, 2002)
Brenda Deen Schildgen's analysis of the Canterbury Tales explores thecontemporary worldviews of medieval Europeans. Chaucer, an Englishcourt poet, wrote probably his greatest work- the Canterbury Tales - at theend of the fourteenth century. It is a collection of 24 tales told by pilgrimsas they make their way to Canterbury cathedral. Chaucer frames the taleswith a prologue and dialogue between the tales.Schildgen's book examines the eight tales set outside Christian Europe.Much of the book discusses the medieval view of paganism and the continuinginfluence of pagan philosophy on medieval intellectual thought.She analyses the "Man of Law's Tale," whose story takes place in bothpagan and Muslim lands. (It is worth pointing out here that, although by thefourteenth century the Mongols increasingly were becoming Muslims, theTartars in the "Squire's Tale" are associated with paganism.) In addition todiscussing the tales involving pagans and Muslims, Schildgen analyzes theanti-Semitic "Prioress' Tale."Drawing on Habermas's theory of practical discourse (in which discussantsengage in a discourse where each is aware of and open to the other'sperspectives and interpretations), Schildgen argues that the Canterbu,yTales is an excellent example of what Habermas has in mind. Traditionalanalysis states that Chaucer does not favor one pilgrim over the others, andSchildgen takes this a step further by arguing that the Canterbury Talesincorporates "a range of intellectual and ethical attitudes that thrived inChaucer's pan-European contemporary cultural and social world." She ...